Criminal Liability for Online Gambling Promotion Perpetrators Through Sports Streaming Services According to Islamic Criminal Law - Sumantoro, Nanda Bagus; Mukhsin, Abd. (IHSA Institute, 2024)
This article discusses the criminal responsibility of individuals promoting online gambling through sports streaming services according to Islamic criminal law and positive law in Indonesia. The background of the problem includes the obligation of streaming service providers to monitor and control promotional content that violates the law and the criminal liabilities that may be imposed on them. The aim of this study is to analyze the mechanisms of content monitoring and control in both positive law and Islamic law, and compare them with regulations in other countries. The method used includes literature review and case analysis. The results indicate that Islamic criminal law prohibits gambling with severe penalties for both perpetrators and facilitators, while Indonesian positive law through the Penal Code and the ITE Law also prohibits online gambling promotion, requiring platform providers to moderate content. However, legal implementation faces technical challenges in detection and enforcement. In conclusion, there is a need for enhanced monitoring systems and stricter law enforcement, along with closer collaboration between service providers and legal authorities to effectively prevent online gambling promotion